DNA Double-Strand Break Repair Inhibitors as Cancer Therapeutics. Issue 1 (22nd January 2015) - Srivastava, Mrinal; Raghavan, Sathees C.
Abstract : Among DNA damages, double-strand breaks (DSBs) are one of the most harmful lesions to a cell. Failure in DSB repair could lead to genomic instability and cancer. Homologous recombination (HR) and nonhomologous end joining (NHEJ) are major DSB repair pathways in higher eukaryotes. It is known that expression of DSB repair genes is altered in various cancers. Activation of DSB repair genes is one of the reasons for chemo- and radioresistance. Therefore, targeting DSB repair is an attractive strategy to eliminate cancer. Besides, therapeutic agents introduce breaks in the genome as an intermediate. Therefore, blocking the residual repair using inhibitors can potentiate the efficacy of cancer treatment. In this review, we discuss the importance of targeting DSB repair pathways for the treatment of cancer. Recent advances in the development of DSB repair inhibitors and their clinical relevance are also addressed. Abstract : DNA double-strand break repair pathways are critical for cell survival. Defective DSB repair is responsible for oncogenesis and imparting resistance to cancer therapy. Therefore, targeting repair is an attractive therapeutic strategy. Advances in developing DSB repair inhibitors and their relevance in cancer therapeutics are discussed.